Humic acid reduces the CuO and ZnO nanoparticles cellular toxicity in rapeseed (Brassica napus) - Yarmohammadi, Afsaneh; Khoramivafa, Mahmud; Honarmand, Saeid Jalali (Cellular and Molecular Biology, 2019)
Concerns about nanoparticles environmental pollution risk have been increased globally due to an increase in the production of nanoparticles in recent years and their use in diverse cases. The purpose of this experiment was to study the alleviation effect of humic acid on nanoparticles toxicity in greenhouse conditions. Thus two separate experiments were conducted at the rosette growing stages of rapeseed in a factorial experiment as a completely randomized design with three replications. The first factor was copper and zinc oxide nanoparticle in five concentrations of 0, 500, 1000, 1500, 2000 mg.L-1 in each of experiments and the second factor was humic acid in two concentrations of 0 and 100 mg.L-1 in both experiments. The results showed that simultaneously application of humic acid and the nanoparticles resulted in increasing of chlorophyll, protein contents, and antioxidants enzymes activity. For example, the maximum activity of catalase was 170.72 and 296.82 µmol.min-1.mg-1 proteins when CuO nanoparticle was utilized alone and together with humic acid respectively. Also increasing the concentration of CuO nanoparticle reduced protein content from 2.44 to 1.88 (mg.gr-1 Fresh leaf weight), while its range was 2.86 and 2.49 (mg.gr-1 Fresh leaf weight) when adding the humic acid. Transmission electron microscopy images of root tissue confirm the decreasing of nanoparticles entrance to plant cell and tissue by humic acid. In general, application of humic acid alleviated the nanoparticles toxicity, due to the high adsorption capacity that is able to get out the metals from plants or like-hormonal activity probably.